2009
DOI: 10.1017/s1368980008004321
|View full text |Cite
|
Sign up to set email alerts
|

Do dietary patterns in older men influence change in homocysteine through folate fortification? The Normative Aging Study

Abstract: Objective: We aimed to describe the difference in B-vitamin intake and in plasma B-vitamin and homocysteine concentrations before and after folic acid fortification, in relation to dietary patterns. Design: The Normative Aging Study (NAS) is a longitudinal study on ageing. Between 1961 and 1970, 2280 male volunteers aged 21-80 years (mean 42 years) were recruited. Dietary intake data have been collected since 1987 and assessment of plasma B vitamins and homocysteine was added in 1993. Setting: Boston, Massachu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…Another study investigated the levels of folate and hcy in a sample of 354 American males aged 21–88 years, following the folic acid fortification programme in the US. Within this study it was reported that plasma folate increased in all three dietary patterns identified, although plasma hcy decreased in the low fruit and vegetable pattern only ( 76 ) . Limitations of these studies include small sample sizes where one study was limited to males only.…”
Section: Dietary Patterns and Associations With Nutritional Biomarkersmentioning
confidence: 73%
“…Another study investigated the levels of folate and hcy in a sample of 354 American males aged 21–88 years, following the folic acid fortification programme in the US. Within this study it was reported that plasma folate increased in all three dietary patterns identified, although plasma hcy decreased in the low fruit and vegetable pattern only ( 76 ) . Limitations of these studies include small sample sizes where one study was limited to males only.…”
Section: Dietary Patterns and Associations With Nutritional Biomarkersmentioning
confidence: 73%
“…They are not always delivered to lysosomes for degradation, tend to be smaller in size compared to autophagosomes, and impor tantly, canonical autophagy machinery is not necessarily involved in the formation of these vesicles (15,(17)(18)(19)(20)22). Notably, viruses can induce the formation of DMVs from the ER, Golgi apparatus, mitochondria, and other sites in the cell, which may have virus-specific implications for antiviral therapies (19,22,28). Recent evidence has shown that DMV formation is independent of LC3 lipidation machinery in both severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and HCV infection; instead, both viruses appear to rely on the PI3K complex for formation of PI3P in DMV membranes (21,29).…”
mentioning
confidence: 99%